The influence of experimental conditions and intermolecular interaction on the band gap determination. Case study of perylene diimide and carbazole-fluorene derivatives. (20th October 2016) - Filapek, Michał; Matussek, Marek; Szlapa, Agata; Kula, Slawomir; Pająk, Michał
Abstract: The perylene diimide and carbazole-fluorene derivatives are intensively investigated in organic electronic and photovoltaic applications. However, they intermolecular interactions vary considerably. Herein, we present a systematic UV–vis spectroscopy and electrochemical study of intermolecular interaction influence on determination of HOMO, LUMO and band gap. The influence of this type of interactions on photophysical properties with the aid of NMR spectroscopy and DFT calculations was examined. Effect of the electrode type was investigated as well. The cyclic voltammetry results obtained at different species concentrations (including solid state measurements) were compared. We have found that when interactions are strong differences in determined bang gap are significant. Contrary to half wave potential, peak onset was found to be concentration independent. Finally, we have observed that comparison of values from solid state measurement and carried out for diluted species can introduce high inconsistencies in determination of structure/property relationships.